2006
DOI: 10.1002/adem.200500245
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidation During Compaction on the Expansion and Stability of Al Foams Made Via a PM Route

Abstract: The production of Al foams via a powder metallurgy (PM) route is attractive due to the ability to produce near-net-shape components. [1] This method involves mixing Al or Al-alloy powder with a foaming agent, typically TiH 2 , followed by compaction. Heating the compact above its melting point results in expansion, due to gas release from the decomposing foaming agent, leading to a closed-cell foam structure. [2] One major factor for successful foaming via the PM route is to ensure that precursors have a densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the case of TiH 2 -and ZrH 2 -based 'zinc' precursors, some researchers used hot pressing at 350 • C [64], while aluminum was hotpressed at 450 • C. Consolidation temperatures of 400-550 • C for aluminum precursors were also reported elsewhere [91]. In this study, the hot pressing of aluminum-TiH 2 precursors at 550 • C was found to lead to poor foam expansion, partly owing to excessive aluminum oxidation [91]. In an interesting study, Jimenez et al [92] compared hot pressing AlSi11 (using heat-treated TiH 2 ) under vacuum to that carried out in air.…”
Section: Production Of the Bulk Foamable Precursormentioning
confidence: 99%
“…In the case of TiH 2 -and ZrH 2 -based 'zinc' precursors, some researchers used hot pressing at 350 • C [64], while aluminum was hotpressed at 450 • C. Consolidation temperatures of 400-550 • C for aluminum precursors were also reported elsewhere [91]. In this study, the hot pressing of aluminum-TiH 2 precursors at 550 • C was found to lead to poor foam expansion, partly owing to excessive aluminum oxidation [91]. In an interesting study, Jimenez et al [92] compared hot pressing AlSi11 (using heat-treated TiH 2 ) under vacuum to that carried out in air.…”
Section: Production Of the Bulk Foamable Precursormentioning
confidence: 99%
“…This sample series has explicitly been included to rule out a major influence of the oxygen content of Al powders on deviations in expansion characteristics. The parameter as such is known to significantly influence this property, as has, e.g., been shown by Weigand, who determined the effective oxygen content range for pure Al alloys to be between 0.2 and 0.72 wt.% [72], while Asavavisichai reported high expansion for the same material, though in a cold rather than hot compacted state, at oxygen contents 0.24, 0.3 and 0.33 wt.%, with a decrease observed for 0.73 wt.% [73]. The fact that the oxygen content of all powders used falls into this range supports the observation that no significant differences in foamability were found between the two standard sample series without additives and different oxygen content levels.…”
Section: (A)mentioning
confidence: 99%
“…It is indeed found that the oxide content influences stability of both Al7, 262, 263 and Pb179 foams, For less than 0.3% oxide in Al precursors poor stability was noted. More than 0.6% oxide content compromises foam expansion indirectly by its negative impact on powder compaction 7, 263, 264. In general, it is difficult to separate the direct influence of oxides on foam stability, i.e., via stabilization of liquid films, from other effects such as the quality of powder compaction.…”
Section: Metal Powder Based Foaming Processes (“Powder Line”)mentioning
confidence: 99%